1996
DOI: 10.1128/mcb.16.2.496
|View full text |Cite
|
Sign up to set email alerts
|

Double Mutants of Saccharomyces cerevisiae with Alterations in Global Genome and Transcription-Coupled Repair

Abstract: The nucleotide excision repair (NER) pathway is thought to consist of two subpathways: transcription-coupled repair, limited to the transcribed strand of active genes, and global genome repair for nontranscribed DNA strands. Recently we cloned the RAD26 gene, the Saccharomyces cerevisiae homolog of human CSB/ERCC6, a gene involved in transcription-coupled repair and the disorder Cockayne syndrome. This paper describes the analysis of yeast double mutants selectively affected in each NER subpathway. Although ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
92
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 36 publications
12
92
0
Order By: Relevance
“…Since RNAPII stalled at damage may make the damage more accessible to repair enzymes than damage within a nucleosome, this may be considered a form of TRC that is independent of CSB. A mechanism such as this may also constitute the coupling factor (rad 26)-independent pathway of TRC identified in yeast (33). The data presented in this report suggest three indirect roles for CSB in TRC.…”
Section: Discussionsupporting
confidence: 50%
“…Since RNAPII stalled at damage may make the damage more accessible to repair enzymes than damage within a nucleosome, this may be considered a form of TRC that is independent of CSB. A mechanism such as this may also constitute the coupling factor (rad 26)-independent pathway of TRC identified in yeast (33). The data presented in this report suggest three indirect roles for CSB in TRC.…”
Section: Discussionsupporting
confidence: 50%
“…Using this system we have demonstrated that extracts made from rad7, rad16, and rad23 strains failed to efficiently repair AAAF-induced DNA damage. In contrast, an extract made from a rad26 deletion strain retained wild-type levels of in vitro excision repair, in keeping with the demonstrated role of RAD26, the homolog of the human Cockayne syndrome group B gene, in transcription-coupled repair (44,54). Since our yeast transcription extracts also permit efficient transcription by RNA polymerase II, it may be possible, by using a DNA substrate containing an RNA polymerase II promoter, to employ this system to study the role of the Rad26 protein in transcription-coupled repair.…”
Section: Discussionsupporting
confidence: 62%
“…2A shows that extracts made from the rad7 and rad16 deletion strains were completely defective for NER in our cell-free system while the rad23 deletion strain had a reduced ability to repair damaged DNA. In contrast to these results with rad7, rad16, and rad23 strains, an extract prepared from a rad26 deletion strain retained its ability to perform NER in vitro, an expected result given the evidence that the Rad26 protein functions exclusively in the subpathway of transcription-coupled repair (44,53). To confirm that the deficient in vitro NER in the rad7 and rad16 extracts was not due simply to poor extract preparation from these particular strains, in vitro complementation experiments were also performed.…”
Section: Nucleotide Excision Repair In Yeast Cellmentioning
confidence: 94%
See 1 more Smart Citation
“…This residual difference might be attributed to Rhp26-independent TCR. Brouwer and co-workers report that there is a Rad26-independent TCR in S. cerevisiae at the short regions downstream of the promoters of active genes (34,35). The contribution of this Rad26-independent TCR was expressed as the difference in UV survival between a NERϪ strain and a rad16 rad26 double mutant.…”
Section: Discussionmentioning
confidence: 99%